The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10886-010-9764-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-amino Acid Conjugates Diversification in Lepidopteran Caterpillars

Abstract: Fatty acid amino acid conjugates (FACs) have been found in noctuid as well as sphingid caterpillar oral secretions; in particular, volicitin [N-(17-hydroxylinolenoyl)-L-glutamine] and its biochemical precursor, N-linolenoyl-L-glutamine, are known elicitors of induced volatile emissions in corn plants. These induced volatiles, in turn, attract natural enemies of the caterpillars. In a previous study, we showed that N-linolenoyl-L-glutamine in larval Spodoptera litura plays an important role in nitrogen assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 24 publications
0
65
0
1
Order By: Relevance
“…Plants may distinguish the type of attacking herbivore by the perception of herbivore-associated elicitors (3,19,32), but herbivores may also suppress plant responses by elicitors in their saliva (33,34). The elicitors in saliva are often species-specific and diverse in structure (35,36). They range from plant cell wall fragments (37,38), peptides derived from ingested plant proteins (39), to fatty acid-amino acid conjugates (16,40), sulfur-containing fatty acids (41), and enzymes (15,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants may distinguish the type of attacking herbivore by the perception of herbivore-associated elicitors (3,19,32), but herbivores may also suppress plant responses by elicitors in their saliva (33,34). The elicitors in saliva are often species-specific and diverse in structure (35,36). They range from plant cell wall fragments (37,38), peptides derived from ingested plant proteins (39), to fatty acid-amino acid conjugates (16,40), sulfur-containing fatty acids (41), and enzymes (15,42).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary compounds may have evolved to allow herbivores to optimize nitrogen intake (35) or to suppress plant defense responses (33,34). In an evolutionary arms race, plants may have Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the amounts of [ Fig. 5B) (Mori et al 2003;Yoshinaga et al 2010). Based on the composition of FACs in gut contents, synthetic purified Nlinolenoyl-L-glutamine and N-linoleoyl-L-glutamine were used to evaluate eliciting activity in soybeans.…”
Section: Quantification Of the Amounts Of [ 13 C 9 ]Flavonoids In Soymentioning
confidence: 99%
“…FACs belong to a widely distributed family of HAEs present in the OS of a large number of lepidopteran species, including Manduca sexta (Yoshinaga et al, 2010), and they are necessary and sufficient to elicit herbivory-specific responses in several plant species including maize (Zea mays), soybean (Glycine max), eggplant (Solanum melongena), black nightshade (Solanum nigrum), and wild tobacco (Nicotiana attenuata; Alborn et al, 1997;Schmelz et al, 2009;VanDoorn et al, 2010;Bonaventure et al, 2011a). Some of the most abundant FACs are conjugates of Glu and Gln with unmodified or oxidized derivatives of polyunsaturated fatty acids (Alborn et al, 1997;Spiteller and Boland, 2003;VanDoorn et al, 2010;Yoshinaga et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most abundant FACs are conjugates of Glu and Gln with unmodified or oxidized derivatives of polyunsaturated fatty acids (Alborn et al, 1997;Spiteller and Boland, 2003;VanDoorn et al, 2010;Yoshinaga et al, 2010). Recently, it has been demonstrated that FACs are essential for the assimilation of nitrogen by developing larvae (Yoshinaga et al, 2008), making it impossible for the caterpillars to feed stealthily without eliciting a defense response by the plant.…”
Section: Introductionmentioning
confidence: 99%